2020
DOI: 10.2196/22703
|View full text |Cite
|
Sign up to set email alerts
|

Use and Cost-Effectiveness of a Telehealth Service at a Centralized COVID-19 Quarantine Center in Taiwan: Cohort Study

Abstract: Background Telehealth is a recommended method for monitoring the progression of nonsevere infections in patients with COVID-19. However, telehealth has not been widely implemented to monitor SARS-CoV-2 infection in quarantined individuals. Moreover, studies on the cost-effectiveness of quarantine measures during the COVID-19 pandemic are scarce. Objective In this cohort study, we aimed to use telehealth to monitor COVID-19 infections in 217 quarantined … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…Four observational studies assessed the contextual factors related to travel policies 77 , 78 , 79 , 80 . Two studies found that the public was supportive of bordure closure policies but showed concerns about the ability of residents to return and the availability of living supplies, including food and household goods and believed that their life was affected by bordure closure 77 78 .…”
Section: Findings Of Included Studies On Contextual Factorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Four observational studies assessed the contextual factors related to travel policies 77 , 78 , 79 , 80 . Two studies found that the public was supportive of bordure closure policies but showed concerns about the ability of residents to return and the availability of living supplies, including food and household goods and believed that their life was affected by bordure closure 77 78 .…”
Section: Findings Of Included Studies On Contextual Factorsmentioning
confidence: 99%
“…Two studies found that the public was supportive of bordure closure policies but showed concerns about the ability of residents to return and the availability of living supplies, including food and household goods and believed that their life was affected by bordure closure 77 78 . One study found the use telehealth can be a cost-effective strategy to provide timely assessment and care for quarantined individuals 80 while one study found no significant impact of sanctions on the compliance rate with self-quarantine 79 .…”
Section: Findings Of Included Studies On Contextual Factorsmentioning
confidence: 99%
“…Connected devices are dramatically changing many aspects in health care [4][5][6][7]. While in cardiology, the majority of devices are intended to monitor heart rhythm, others have a therapeutic purpose [8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Telemedicine is an effective instrument for monitoring COVID-19 infection in quarantined travelers. 27 However, many physicians are unwilling to participate in telemedicine and many specialists prefer face-to-face visits, which is a problem encountered in promoting telemedicine in Taiwan.…”
Section: Telemedicine In Taiwanmentioning
confidence: 99%